Strategi Strategi Kepala Sekolah dalam Mengelola Konflik Antar Guru di SMKS Bina Mandiri Gorontalo - Desi Novitasari; Fatimatuzzahra Fatimatuzzahra; Salamun Salamun; Abdul Aziz (Lembaga Yasin AlSys, 2025)
This study aims to examine the principal’s strategies in managing inter-teacher conflict at SMKS Bina Mandiri Gorontalo, based on the limited research regarding school leadership roles in conflict management within vocational education settings. Effective conflict resolution plays a critical role in fostering a harmonious and collaborative work environment. A qualitative descriptive method was employed, with data collected through in-depth interviews with the principal and three teachers selected using purposive sampling. Thematic analysis was used to identify patterns in conflict resolution strategies. The findings reveal that inter-teacher conflicts are generally triggered by differences in teaching methods, miscommunication, and imbalances in task distribution. The principal adopted mediation and participatory approaches, including deliberation, open dialogue, self-reflection, and fair and transparent decision-making. These strategies were positively received by the teachers, as they contributed to improving working relationships and enhancing team synergy. The main conclusion of this study is that successful conflict resolution is significantly influenced by the principal’s emotional intelligence and dialogical competence. These findings contribute to the literature on human resource management in education and offer practical recommendations for school principals to strengthen interpersonal communication and build a supportive and conducive work environment.